Evolution of soft-phonon modes in Fe–Pd shape memory alloy under large elastic-like strains. (15th February 2016) - Seiner, Hanuš; Stoklasová, Pavla; Sedlák, Petr; Ševčík, Martin; Janovská, Michaela; Landa, Michal; Fukuda, Takashi; Yamaguchi, Takashi; Kakeshita, Tomoyuki
Abstract: We study elastic anisotropy of a disordered Fe–Pd alloy under reversible elastic-like strains up to 4.3% by means of ultrasonic methods. The evolution of the full tetragonal tensor of elastic constants with a [001]-prestress ranging from 0 to 200 MPa is obtained, which enables an analysis of the change of the low-frequency limit of the soft-phonon structure. It is observed that while the anisotropy of the elastic moduli further increases, giving rise to an anomalous anisotropy factor of A  > 50, the phonon branches stiffen. This means that, unlike for conventional shape memory alloys, the tetragonal crystal structure induced by the prestress is more stable than the stress-free cubic structure, although there is no other indication of the stress-induced transition. Graphical abstract: